`6x-5z=17` -----(1)

`5x-y+3z=-1` ----(2)

`2x+y=-41` ----(3)

`(1)+(3)`

`8x+y-5z = -24` -----(4)

`(2)+(4)` ---> y will cancel out.

`13x-2z = -25 ` ----(5)

`(1)*2-(5)*5` ----> z will cancel out

`12x-65x = 17*2+25*5`

`-53x = 159`

`x = -3`

From (5)

`z = (-25-13*(-3))/(-2) = -7`

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`6x-5z=17` -----(1)

`5x-y+3z=-1` ----(2)

`2x+y=-41` ----(3)

`(1)+(3)`

`8x+y-5z = -24` -----(4)

`(2)+(4)` ---> y will cancel out.

`13x-2z = -25 ` ----(5)

`(1)*2-(5)*5` ----> z will cancel out

`12x-65x = 17*2+25*5`

`-53x = 159`

`x = -3`

From (5)

`z = (-25-13*(-3))/(-2) = -7`

From (3)

`y = -41-2*(-3) = -35`

*So the answers are;*

*x = 2*

*y = -35*

*z = -7*